An SP-Tree-Based Web Service Matching Algorithm Considering Data Provenance. Issue 4 (2nd October 2017) - Xu, Guoyan; Luo, Jianxiang; Lv, Xin; Yang, Li; Tang, Ming
Abstract: Currently the semantic-based Web service matching has improved the precision ratio of service discovery. But it can't distinguish between different data on the different needs of the service, due to rarely considering the input data provenance of Web services. That is an important contribution of high precision ratio. Therefore, in this paper, for further improving the accuracy of Web service matching, the data provenance is considered as a constraint attribute of Web service matching. Firstly, an SP-tree-based Web service matching algorithm considering data provenance (SMDP) is proposed, consisting of three aspects: The general algorithm thoughts, the data How provenance matching calculation method, (which is mainly introduced for it is the hardest calculation part), and the experiments verifying precision ratio of SMDP is 10% higher than the traditional semantic-based matching. Secondly, a Web service matching model based on SMDP is designed and a prototype system for water resources application is implemented, which confirms the feasibility and effectiveness of SMDP, especially, the importance of data How provenance in service matching.